Bithiazole Inhibitors of Phosphatidylinositol 4‐Kinase (PI4KIIIβ) as Broad‐Spectrum Antivirals Blocking the Replication of SARS‐CoV‐2, Zika Virus, and Human Rhinoviruses. (7th September 2021) - Grazia Martina, Maria; Vicenti, Ilaria; Bauer, Lisa; Crespan, Emmanuele; Rango, Enrico; Boccuto, Adele; Olivieri, Noemi; Incerti, Matteo; Zwaagstra, Marleen; Allodi, Marika; Bertoni, Simona; Dreassi, Elena; et al.
Abstract: Over half a century since the description of the first antiviral drug, "old" re‐emerging viruses and "new" emerging viruses still represent a serious threat to global health. Their high mutation rate and rapid selection of resistance toward common antiviral drugs, together with the increasing number of co‐infections, make the war against viruses quite challenging. Herein we report a host‐targeted approach, based on the inhibition of the lipid kinase PI4KIIIβ, as a promising strategy for inhibiting the replication of multiple viruses hijacking this protein. We show that bithiazole inhibitors of PI4KIIIβ block the replication of human rhinoviruses (hRV), Zika virus (ZIKV) and SARS‐CoV‐2 at low micromolar and sub‐micromolar concentrations. However, while the anti‐hRV/ZIKV activity can be directly linked to PI4KIIIβ inhibition, the role of PI4KIIIβ in SARS‐CoV‐2 entry/replication is debated. Abstract : Host targeting is a promising approach for the development of broad‐spectrum antiviral agents (BSAAs) endowed with a high genetic barrier to resistance and efficacy against viral mutants resistant to conventional antiviral drugs. We show that bithiazole inhibitors of the host lipid kinase PI4KIIIβ block the replication of human rhinoviruses (hRV), Zika virus (ZIKV) and SARS‐CoV‐2 at low micromolar and sub‐micromolar concentrations. Moreover, inhibition of SARS‐CoV‐2 entry seems to be connected with an additional unknown target.